Citizens, Subjects or Tyrants? Relocating the People in Pocock's The Machiavellian Moment. Issue 2 (17th February 2017) - Banerjee, Kiran; Suchowlansky, Mauricio
SUMMARY: J.G.A. Pocock's The Machiavellian Moment played a pivotal role in inaugurating the important turn toward the classical republican tradition in the history of political thought. In this revival of republicanism, the people are primarily presented as integral to combining active political participation and military prowess in the context of a common defence of liberty against foreign and domestic tyranny. In this essay we wish to revisit the role of the people in Pocock's interpretation of Machiavelli's republican thought. In doing so, we wish to bring Pocock's contentions relative to the governo popolare one step further by introducing and analysing Machiavelli's expositions of popular behaviour in the context of the Florentine Histories . Contrary to Pocock's assumptions, the Florentine Histories shows how Machiavelli became substantively more critical of the people as a sound political agent. We demonstrate this by reconstructing important shifts in the presentation of the people apparent in this later work, suggesting a number of important elaborations to Machiavelli's understanding of both the people and citizenship.